School travel route measurement and built environment effects in models of children’s school travel behavior - Kristian Larsen; Ron N Buliung; Guy EJ Faulkner (Journal of Transport and Land Use, 2015)
The most common form of physical activity for people of all ages is walking, thus the use of active travel modes, such as walking or cycling for school trips, can increase daily physical activity levels. School travel is one way to encourage walking and cycling on a daily basis. Much of the recent literature reports inconsistent results pertaining to how the built environment may relate to active school travel. To date, there is no consistent approach toward conceptualizing the “environment” for its measurement, and this may be partially to blame for the inconsistent results. The purpose of this paper is twofold: to examine how characteristics of the built environment might relate to mode of school travel, while testing how measurement of the environment may influence the results in terms of the shortest path or respondent reported route mapping. The results indicate that model parameter estimates vary when using these two route measurement methods. Differences in the conceptualization and measurement of the school travel environment could carry forward into misguided planning or policy interventions targeting environmental features that may actually have no influence on school travel decisions.